Opsin Expression in Human Epidermal Skin. (13th November 2014) - Haltaufderhyde, Kirk; Ozdeslik, Rana N.; Wicks, Nadine L.; Najera, Julia A.; Oancea, Elena
Abstract Human skin is constantly exposed to solar light containing visible and ultraviolet radiation (UVR), a powerful skin carcinogen. UVR elicits cellular responses in epidermal cells via several mechanisms: direct absorption of short‐wavelength UVR photons by DNA, oxidative damage caused by long‐wavelength UVR, and, as we recently demonstrated, via a retinal‐dependent G protein‐coupled signaling pathway. Because the human epidermis is exposed to a wide range of light wavelengths, we investigated whether opsins, light‐activated receptors that mediate photoreception in the eye, are expressed in epidermal skin to potentially serve as photosensors. Here we show that four opsins—OPN1‐SW, OPN2, OPN3 and OPN5—are expressed in the two major human epidermal cell types, melanocytes and keratinocytes, and the mRNA expression profile of these opsins does not change in response to physiological UVR doses. We detected two OPN3 splice variants present in similar amounts in both cell types and three OPN5 splice isoforms, two of which encode truncated proteins. Notably, OPN2 and OPN3 mRNA were significantly more abundant than other opsins and encoded full‐length proteins. Our results demonstrate that opsins are expressed in epidermal skin cells and suggest that they might initiate light–induced signaling pathways, possibly contributing to UVR phototransduction.